MENUJU TRANSFORMASI: PENDIDIKAN PASTORAL KONSELING SEBAGAI JEMBATAN KESEJAHTERAAN JIWA - Apriani Legrans; Meifira Tanor; Joshua Tuerah; Yohan Brek (PT. GIAT KONSELING NUSANTARA, 2024)
In today's rapidly changing world, mental well-being is a critical aspect of human life. The complexities of modern living often lead to stress, anxiety, and disillusionment, compromising mental health. As holistic beings comprising body, soul, and spirit, achieving mental well-being cannot be separated from spiritual dimensions. This study explores the role of pastoral counseling education as a bridge to mental well-being, particularly within the Christian faith. By integrating spiritual and psychological perspectives, this research aims to provide a comprehensive understanding of mental well-being, addressing the intricate relationships between interpersonal relationships, work, and life's meaning. Ultimately, this study seeks to contribute to the development of a transformative pastoral counseling approach that fosters mental well-being, promoting a deeper sense of peace and wholeness that transcends human understanding